GRAPHIC METHOD OF DECISION OF TASKS WITH PARAMETERS BY MEANS OF PPM OF " LIBRARY OF ELECTRONIC VISUAL AIDS. ALGEBRA, 7-9 FORMS" (Journal of Information Technologies in Education (ITE), 2010)
This article is sanctified to possibilities of the use of pedagogical programmatic mean " Library of electronic visual aids. Algebra, 7-9 forms" teachers of mathematics at exposition of theme of "Task with parameters" by a method evidently - graphic interpretations.
Keywords: graphic method; school systems of computer algebra; tasks with parameters